(untitled) (Journal of Organizational Psychology, 2019)
Training is an important segment of HRM practices, which supports the retention and development of employees because of the training given to employees. This research explored literature on strategic training and development approaches that leads to the retention of talented employees and classifies the different strategic methods into a framework.